A qualitative analysis about the housing policy in Spain.The experts opinion - Palacios García, Antonio J.; Vinuesa Angulo, Julio (Anales de Geografía de la Universidad Complutense, 2010)
In Spain the information about the housing park and market is clearly insufficient. In consequence the analysis about the housing problem and the own policies applied to solved it has important weakness. It has turned to the opinion of experts in analysis and management to advance in the knowledge and it has been synthesized by application of the Delphi method. By means of it, it has been consulted the characteristics of housing policies and phenomenon of the unoccupied housing. From them some reflections have been done about the nature of problems and policies applied and some proposals to improve the situation.